2013
DOI: 10.1073/pnas.1222726110
|View full text |Cite
|
Sign up to set email alerts
|

Specialized bat tongue is a hemodynamic nectar mop

Abstract: Nectarivorous birds and bats have evolved highly specialized tongues to gather nectar from flowers. Here, we show that a nectar-feeding bat, Glossophaga soricina , uses dynamic erectile papillae to collect nectar. In G. soricina , the tip of the tongue is covered with long filamentous papillae and resembles a brush or mop. During nectar feeding, blood vessels within the tongue tip become engorged with blood and the papillae become erect. Tumescence and papilla er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
74
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 22 publications
0
74
0
1
Order By: Relevance
“…Similar to those of extant nectarivorous phyllostomids, these molars are narrow, and their cusps are reduced lingually and flattened labially [1,8]. The two primarily nectarivorous phyllostomid subfamilies, Glossophaginae and Lonchophyllinae, share adaptations for acquiring nectar including an elongated rostrum and palate, reduced dentition and elongated tongues [8][9][10]. These phyllostomids compose a phenotypic optimum that prevents eating hard foods such as beetles or figs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to those of extant nectarivorous phyllostomids, these molars are narrow, and their cusps are reduced lingually and flattened labially [1,8]. The two primarily nectarivorous phyllostomid subfamilies, Glossophaginae and Lonchophyllinae, share adaptations for acquiring nectar including an elongated rostrum and palate, reduced dentition and elongated tongues [8][9][10]. These phyllostomids compose a phenotypic optimum that prevents eating hard foods such as beetles or figs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The drinking patterns of animals such as cats (Reis et al, 2010), dogs (Crompton and Musinsky, 2011), bats (Harper et al, 2013) and hummingbirds (Kim et al, 2012;Rico-Guevara and Rubega, 2010) have been observed and analysed explicitly to varying degrees in previous studies. The dynamic surfaces, categorized as the erectable hairs, setae and filamentous papillae, play an important role in improving the ability of trapping liquid food (Harper et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic surfaces, categorized as the erectable hairs, setae and filamentous papillae, play an important role in improving the ability of trapping liquid food (Harper et al, 2013). A honeybee is a typical insect whose proboscis has been studied widely, for instance, in relation to gustation preferences (Heyneman, 1983;Tan et al, 2014) and nectar lapping strategies .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations